2018
DOI: 10.1002/cne.24505
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of pineal microglia to surgical versus pharmacological stimuli

Abstract: Microglial cells are one of the interstitial elements of the pineal gland (PG). We recently reported the pattern of microglia colonization and activation, and microglia-Pax6+ cell interactions during normal pineal ontogeny. Here, we describe the dynamics of microglia- Pax6+ cell associations and interactions after surgical or pharmacological manipulation. In adult rats, the superior cervical ganglia (SCG) were exposed, and either bilaterally excised (SCGx) or decentralized (SCGd). In the SCGx PGs, the density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 93 publications
1
24
0
Order By: Relevance
“…A new frame for understanding pineal biology was recently provided by sequencing the transcriptome of individual cells (28,30). This study at single-cell resolution confirmed the high cellular heterogeneity within the rat PG, as it was previously proposed (32)(33)(34)(35)(36). These PG cell types were found to be transcriptionally distinct: two melatonin-producing pinealocyte subtypes (alpha and beta), three astrocyte subpopulations, two microglia subtypes, vascular and leptomeningeal cells, and endothelial cells (30).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…A new frame for understanding pineal biology was recently provided by sequencing the transcriptome of individual cells (28,30). This study at single-cell resolution confirmed the high cellular heterogeneity within the rat PG, as it was previously proposed (32)(33)(34)(35)(36). These PG cell types were found to be transcriptionally distinct: two melatonin-producing pinealocyte subtypes (alpha and beta), three astrocyte subpopulations, two microglia subtypes, vascular and leptomeningeal cells, and endothelial cells (30).…”
Section: Introductionsupporting
confidence: 77%
“…SCGx and sham-operated animals (N = 4 per each group) were housed in a stress-free environment for three weeks to prevent pinealocyte activation by stress-induced catecholamines. The Wallerian degeneration of the sympathetic nerve fibers from the SCG and the subsequent inflammatory environment within the PG were ameliorated at this post-surgical time point (34,48). Following this surgical recovery, the rats were sacrificed at ZT14 (early night).…”
Section: Surgical Removal Of Superior Cervical Gangliamentioning
confidence: 99%
“…More recently, autophagy has been related to microglia in CNS senescence and disease (Plaza-Zabala et al, 2017). Our studies in the rat pineal gland and also cerebral cortex research by other investigators have revealed that precursorlike cells without signs of death or classic apoptosis were approached and internalized by microglial cells (Cunningham et al, 2013;Ibañez Rodriguez et al, 2016;Ibañez Rodriguez et al, 2018). Mechanisms for cell disposal by microglia are not well understood, especially in the pineal gland, and further research is needed under both normal and insult-responsive conditions.…”
Section: Biocellmentioning
confidence: 67%
“…In the pineal gland of young adult rats, we observed that microglia-Pax6 + cell interactions were modified by the local milieu. Surgical or pharmacological insults impacted differentially on the regulation of the Pax6 + cell population by microglia, even though clustered microgliosis was commonly observed (Ibañez Rodriguez et al, 2018). The impact of microglia-Pax6 + cell interactions in the senescent pineal gland is still unknown (Fig.…”
Section: Biocellmentioning
confidence: 99%
“…Bilateral superior cervical ganglionectomy (SCGx) was performed as previously described [17,19,20,54]. Briefly, under ketamine/xylazine anesthesia (50 mg/kg of body weight and 5 mg/kg of body weight, respectively), the ventral neck region was shaved and disinfected.…”
Section: Surgerymentioning
confidence: 99%